PEMBERIAN BANTUAN HUKUM BAGI ANGGOTA POLRI MELALUI PENERAPAN MEDIASI PENAL DALAM PENYELESAIAN TINDAK PIDANA - Mayendi, Eri (Universitas Ekasakti, 2019)
The provision of legal assistance by the Regional Police Law is regulated in the Regulation of the Head of the Republic of Indonesia National Police Number 2 of 2017 concerning Procedures for Providing Legal Aid by the Indonesian National Police. The specifications in this study are descriptive analytical. The results of the study are First, Implementation of the settlement of criminal acts by applying penal mediation by legal counsel from the legal field of the Regional Police is to play a role in encouraging or proposing the selection of case settlement in non-litigation, facilitating the implementation of reasoning mediation, and becoming mediators. Advocates offer mediation only to apology or peace statements without being able to eliminate criminal justice processes for perpetrators. Victims who are not willing to be resolved by reason mediation and still demand that the case continue to the next stage as well as uncooperative suspects and the lack of understanding of the community regarding the use of reasoning mediation. They consider the reasoning mediation process pursued by legal advisors originating from the Polda legal field is an effort to free criminal offenders who have harmed the community.